AWARENESS OF NEUROMARKETING AMONG THE SELECTED INDIGENOUS STARTUPS OF NORTH EAST INDIA - Gogoi, Pinky; Mochahari, Subung (The journal of contemporary issues in business and government, 2021)
The traditional methods are fading away with the scientific methods taking a plunge into the field of market research. Neuro marketing is the recent technique in the field of market research that is attracting many eye-balls. It applies neuropsychology to marketing research. Human decision-making is both a conscious and non-conscious process in the brain, and while this method of research succeeded in gathering explicit (or conscious) emotions, the traditional methods failed to gain the consumer's implicit (or unconscious) emotions. Non-conscious information has a large influence in the decision-making process. The goal of the present study is to analyze the Awareness of Neuro marketing as a tool for studying Consumer behavior among the indigenous North- Eastern startups of India. This concept is less known and unexplored not only in Assam but the whole of North-East, yet the startups do not ignore the fact that studying consumer psychology is an important aspect. As Neuromarketing further evolves, we can expect more and more revelation of intricacies involved which determines the consumer‟s purchasing behavior. The awareness of Neuromarketing is to be studied in order to know its application, success and failure as a tool for studying consumer behavior as this type of studies have an important role for the future of marketing.The study will help the local entrepreneurs and marketers to know about Neuromarketing and upgrade their tools and techniques for studying consumer behavior.